Optimization of Laccase Production using White Rot Fungi and Agricultural Wastes in Solid-State Fermentation - Risdianto, Hendro; Sofianti, Elis; Suhardi, Sri Harjati; Setiadi, Tjandra (Journal of Engineering and Technological Sciences, 2012)
Abstract. Laccase has been produced in a solid-state fermentation (SSF) process using white rot fungi and various  lignocellulose-based substrates.  The white  rot fungi  used  were  Marasmius  sp.,  Trametes  hirsuta,  Trametes  versicolor  and Phanerochaete  crysosporium.  The  solid  substrates  employed  in  this  research were collected from  agricultural  waste, specifically  empty fruit bunches (EFB), rice  straw,  corncobs  and  rice  husks.  The  objective  of  this  research  was  to determine  the  most  promising  fungus,  the  best  solid  substrate  and  the  optimal conditions for the production of laccase.  The  results showed that  Marasmius  sp. on all solid substrates displayed  a  higher laccase activity than that of  any  other strain  of  white  rot  fungi.  Marasmius  sp.  and  a  solid  substrate  of  rice  straw demonstrated  the  highest  laccase  activity  of  1116.11  U/L  on  day  10.  Three significant  factors,  i.e.  pH,  temperature  and  yeast  extract  concentration,  were studied by  the  response surface method on laccase production using  Marasmius sp.  and rice straw. The optimized conditions were  a  pH, temperature and yeast extract concentration of 4.9, 31ºC and 0.36 g/L,  respectively.  The fermentation of  Marasmius  sp.  in  SSF  on agricultural  waste  shows  a  great  potential  for  the production of laccase.